Targeting interstrand crosslink repair to improve chemotherapeutic strategies - Castle, L (2017)
Many clinically effective chemotherapeutic agents exert their toxicity through formation of DNA interstrand cross-links (ICL). These prevent the replication and transcription of DNA and if unrepaired lead to cell death. Despite the success of ICL inducing agents in treating cancers, issues remain with a lack of sensitivity in some tumours, therapy-limiting toxicity and acquired resistance and tumour recurrence. The modulation of ICL repair could improve chemotherapy outcomes and the specific targeting of ICL repair in quiescent cells may selectively target cancer stem cells and ameliorate issues with recurrence. This thesis seeks to identify potential druggable targets that may sensitise cancer cells to ICL inducing agents and elucidate the role of ICL repair in quiescence. Previous studies have suggested ICL repair occurs chiefly in S-phase when DNA replication forks collide with ICLs. However, recent research in budding yeast, using Xenopus cell-free extracts and using genetic reporter assays in mammalian cells suggests that ICL repair can occur in the G1 phase of the cell cycle via the nucleotide excision repair (NER) and translesional synthesis (TLS) pathways. Previously this G1 pathway had not been well explored in mammalian cells. In this thesis a model for G1 ICL repair was created using a mammalian cell line. Flow cytometry analysis (FACS) of cell cycle dynamics following ICL induction in phase G1 demonstrated that repair of ICL can occur in G1 and this appears time dependent. Further analysis by FACS, comet assays and cell survival analysis confirmed repair of ICL in G1 and suggested that the NER factors XPF, XPB and XPD and the exonucleases SNM1A and EXO1 may be required for ICL repair in G1 but not the XPG, FAN1 or CSB repair proteins. Along-side these studies, a large-scale siRNA screen of 640 DNA damage repair genes was performed in a lung cancer cell line utilising colony formation assays to identify potential cisplatin and radiotherapy sensitising genes. Following a secondary screen, eight potential radiation and cisplatin sensitising genes were identified and examined in further detail, with the gene PIF1 finally confirmed in CRISPR/Cas9 knockout cells as a potential cisplatin sensitising gene. The findings in this thesis confirm ICL repair can occur in G1 in mammalian cells and identify PIF1 as a potential cisplatin sensitiser in human cells. In the future, targeting of the specific endonucleases responsible for G1 ICL repair or PIF1 may offer a potential clinical cancer treatment option.